2022
DOI: 10.3390/plants11111414
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Resistance of Eleven Maize Races (Zea mays L.) to the Red Spider Mite (Tetranychus merganser, Boudreaux)

Abstract: At least 59 maize races (Zea mays L.) have been registered in Mexico. The feeding damage caused by insects and mites to maize crops generates up to ~30% of maize yield losses. Spider-mite-resistant plants are needed. The red spider mite, Tetranychus merganser Boudreaux (Acari: Tetranychidae), is distributed in the United States, China, Mexico, and Thailand. It is considered a potential pest in Mexican agriculture. The aim of this study was to evaluate the resistance mechanisms (antixenosis and antibiosis) of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
1
2
Order By: Relevance
“…Little has been reported on TSP content in ‘EO’ land-race samples. In this regard, Ballesteros Martínez et al [ 6 ] reported values lower than those found in this work, ranging from 100 to 130 mg FAE g −1 ds, while Rocandio-Rodríguez et al [ 32 ] reported 344 mg GAE 100 g −1 ds in a cross of Elotes Occidentales × Tuxpeño. Regarding TA content, a trend of interaction with the environment was observed across years, with values of 10.5, 17.0, and 15.2 mg PCE 100 g −1 ds for Pz1 in cycles 2019, 2020, and 2021, respectively, and 12.9, 15.9, and 18.1 mg PCE 100 g −1 ds for Pz2 in the same years ( Figure 2 B).…”
Section: Resultscontrasting
confidence: 78%
“…Little has been reported on TSP content in ‘EO’ land-race samples. In this regard, Ballesteros Martínez et al [ 6 ] reported values lower than those found in this work, ranging from 100 to 130 mg FAE g −1 ds, while Rocandio-Rodríguez et al [ 32 ] reported 344 mg GAE 100 g −1 ds in a cross of Elotes Occidentales × Tuxpeño. Regarding TA content, a trend of interaction with the environment was observed across years, with values of 10.5, 17.0, and 15.2 mg PCE 100 g −1 ds for Pz1 in cycles 2019, 2020, and 2021, respectively, and 12.9, 15.9, and 18.1 mg PCE 100 g −1 ds for Pz2 in the same years ( Figure 2 B).…”
Section: Resultscontrasting
confidence: 78%
“…Little has been reported on TSP content in 'EO' land-race samples. In this regard, Ballesteros Martínez et al [6] reported values lower than those found in this work, ranging from 100 to 130 mg FAE g −1 ds, while Rocandio-Rodríguez et al [32] reported 344 mg GAE 100 g −1 ds in a cross of Elotes Occidentales × Tuxpeño. Regarding TA content, a trend of interaction with the environment was observed across years, with values of 10.5, 17.0, and 15.2 mg PCE 100 g −1 ds for Pz1 in cycles 2019, 2020, and 2021, respectively, and 12.9, 15.9, and 18.1 mg PCE 100 g −1 ds for Pz2 in the same years (Figure 2B).…”
Section: Phytochemical Components 251 Total Soluble Phenols (Tsps) An...contrasting
confidence: 73%
“…Among the inbred lines studied here, CML71 is revealed as a highly promising line for use in breeding for native genetic resistance to FAW in tropical maize. Its resistance to FAW can be due to chemical characteristics present in the leaves as shown by [42] from a specific maize race to red spider mite. Chemical characteristics have been reported to confer resistance to FAW damage in maize such as the presence of jasmonic acid [30], (E)-β-caryophyllene [39], cuticular lipids [38,43,44], silica [45,46], high induced defensive transcriptomic signatures and higher levels of benzoxazinoids [47].…”
Section: Discussionmentioning
confidence: 99%